2016
DOI: 10.1186/s12866-016-0771-y
|View full text |Cite
|
Sign up to set email alerts
|

RsmW, Pseudomonas aeruginosa small non-coding RsmA-binding RNA upregulated in biofilm versus planktonic growth conditions

Abstract: BackgroundBiofilm development, specifically the fundamentally adaptive switch from acute to chronic infection phenotypes, requires global regulators and small non-coding regulatory RNAs (sRNAs). This work utilized RNA-sequencing (RNA-seq) to detect sRNAs differentially expressed in Pseudomonas aeruginosa biofilm versus planktonic state.ResultsA computational algorithm was devised to detect and categorize sRNAs into 5 types: intergenic, intragenic, 5′-UTR, 3′-UTR, and antisense. Here we report a novel RsmY/RsmZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
82
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 76 publications
0
82
0
Order By: Relevance
“…A suicide vector was generated using In‐Fusion HD cloning kit (Clontech Laboratories), as described previously (Miller et al., ), which allowed for deletion of the pa1595 gene through allelic exchange with an antibiotic cassette, pucGM. Briefly, primers were designed according to the manufacturer's suggestion (Table S1) 1 kb upstream and downstream regions of the pa1595 gene were amplified by PCR from P. aeruginosa chromosome.…”
Section: Methodsmentioning
confidence: 99%
“…A suicide vector was generated using In‐Fusion HD cloning kit (Clontech Laboratories), as described previously (Miller et al., ), which allowed for deletion of the pa1595 gene through allelic exchange with an antibiotic cassette, pucGM. Briefly, primers were designed according to the manufacturer's suggestion (Table S1) 1 kb upstream and downstream regions of the pa1595 gene were amplified by PCR from P. aeruginosa chromosome.…”
Section: Methodsmentioning
confidence: 99%
“…However, here we present a model where small RNA regulation is dependent on the conditions in which we study P. aeruginosa (i.e., broth versus surface) which favor two different bacterial lifestyles. Furthermore, RsmW a novel RNA under the control of the Gac system has been identified to be strongly upregulated in biofilm conditions compared to planktonic cultures which further strengthens the existence of differential genetic regulation depending on the selected growth conditions (Miller et al, 2016). Our data confirm that the GacS/GacA system is not the only one responsible for the control of rsmZ expression and implicates the presence of unidentified key factors that are important when cells are grown on a surface rather than in planktonic cultures, as exemplified by the use of swarming motility as a model for surface behavior ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 68%
“…Both of these findings are consistent with RsmV serving a role in RsmA/RsmF sequestration. When compared to the previously identified sequestering RNAs RsmW, RsmY, and RsmZ (13, 31), RsmV demonstrated activity comparable to RsmY when using the P tssA1’-‘lacZ reporter (Fig. 3B) and had the strongest inhibitory activity for the P exsD-lacZ reporter (Fig.…”
Section: Resultsmentioning
confidence: 80%
“…Transcription of rsmY and rsmZ is controlled by the GacAS two component system (20). A previous study found that GacAS does not control rsmW transcription (31). To determine whether rsmV transcription is regulated by GacA, a P rsmV-lacZ transcriptional reporter was integrated at the ΦCTX phage attachment site of wt cells and a ∆ gacA mutant.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation